COLLABORATIVE GOVERNANCE DALAM PENGELOLAAN OBJEK REKREASI TAMAN HUTAN RAYA SULTAN SYARIF HASYIM DI KECAMATAN MINAS KABUPATEN SIAK PROVINSI RIAU TAHUN 2022-2023 - Nanda, Ayi Fiksa; ,, Adlin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The management of the Sultan Syarif Hasyim Grand Forest Park is carried out by the Technical Implementation Unit of the Minas Model Production Forest Management Unit, which is the technical task executor, established by the Riau Provincial Forestry and Environment Service. The SSH Forest Park (Tahura SSH) is also being prepared as a natural tourism destination for the surrounding community. The purpose of this study was to determine collaborative governance in the management of the Sultan Syarif Hasyim Grand Forest Park recreational object and to identify the inhibiting factors in the management of the Sultan Syarif Hasyim Grand Forest Park recreational object in Minas District, Siak Regency, Riau Province, in 2022-2023. This research method uses a qualitative descriptive approach. The data used in this study is descriptive, presenting the results of research on Collaborative Governance in the Management of the Sultan Syarif Hasyim Grand Forest Park Recreation Site in Minas District, Siak Regency, Riau Province, in 2022-2023. Data collection techniques used in this study included interviews, documentation, and observation. The results showed that Collaborative Governance has been implemented, but not optimally. Three indicators, namely face-to-face meetings, building trust, and commitment to the process, have not been fully implemented between the UPT KPHP Minas Tahura and other stakeholders. Other obstacles encountered in the Collaborative Governance process are a lack of quality and quantity of human resources, inadequate facilities and infrastructure, and minimal budget allocation for the Management of the Sultan Syarif Hasyim Grand Forest Park Recreation Site. Keywords: Collaborative Governance, Management, Grand Forest Park